1236. Infection Control Risk Mitigation and Implementation of Best Practice Recommendations in Long-Term Care Facilities. (26th November 2018) - Fitzgerald, Teresa; Nailon, Regina; Tyner, Kate; Beach, Sue; Drake, Margaret; Micheels, Teresa; Rupp, Mark E; Schwedhelm, Michelle; Tierney, Maureen; Ashraf, Muhammad Salman
Abstract: Background: Nebraska (NE) Infection Control Assessment and Promotion Program (ICAP) is a quality improvement initiative supported by the NE Department of Health and Human Services. This initiative utilizes subject matter experts (SMEs) including infectious diseases physicians and certified infection preventionists (IP) to assess and improve infection prevention and control programs (IPCP) in various healthcare settings. NE ICAP conducted on-site surveys and observations of IPCP in many volunteer facilities to include long-term care facilities (LTCF) between November 2015 and July 2017. SMEs provided on-site coaching and made best practice recommendations (BPR) for priority implementation. Impact of this intervention on LTCF IPCP was examined. Methods: Using a standardized questionnaire, follow-up phone calls were made with LTCF to evaluate implementation of the BPR one-year post-assessment. Descriptive analyses were performed to examine BPR implementation in LTCF that had follow-up between 4/4/17 to 4/17/18 and to identify factors that promoted or impeded BPR implementation. Results: Overall, 45 LTCF were assessed. The top 5 IC categories requiring improvement were audit and feedback practices (28 of 45, 62%), PPE supplies at point of use (62%), IC risk assessments (58%), TB risk assessments (56%), and supply and linen storage practices (56%). Follow-up assessments were completed for 270 recommendations in 25 LTCF. Recommendations reviewed ranged from three to 26 per LTCF (median = 15). The majority of the 270 recommendations ( n = 162, 60%) had been either completely (35%) or partially (25%) implemented by the time of the follow-up calls. The ICAP visit itself was reported as the most helpful resource for BPR implementation (77 of 162). Lack of staffing was the most commonly mentioned barrier to implementation when LTCF implemented BPR partially or implementation was not planned (37 of 85). BPR Implementation most frequently involved additional staff training (64 of 162), review of policies and procedures (38 of 162), and implementing audit (34 of 162) and/or feedback (23 of 162) programs. Conclusion: Numerous IC gaps exist in LTCF. Peer-to-peer feedback and coaching by SMEs facilitated implementation of many BPR directed toward mitigating identified IC gaps. Disclosures: All authors: No reported disclosures.